2021
DOI: 10.3390/molecules26237140
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cinnamaldehyde and Thymol from PLA/Tilapia Fish Gelatin-Sodium Alginate Bilayer Films to Liquid and Solid Food Simulants, and Japanese Sea Bass: A Comparative Study

Abstract: This study aimed to develop an active biodegradable bilayer film and to investigate the release behaviors of active compounds into different food matrices. Cinnamaldehyde (CI) or thymol (Ty) was encapsulated in β-cyclodextrin (β-CD) to prepare the active β-CD inclusion complex (β-CD-CI/β-CD-Ty). The tilapia fish gelatin-sodium alginate composite (FGSA) containing β-CD-CI or β-CD-Ty was coated on the surface of PLA film to obtain the active bilayer film. Different food simulants including liquid food simulants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…This means that a higher percentage of AITC was released from the films to the fatty simulant. This is the most common behavior for active materials with compounds derived from essential oils, which is related to the hydrophobic nature of the compound [ 41 , 42 , 43 ]. In previous sections, it was observed that the surface free energy of materials was dominated by the polar component ( γ S P > γ S D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that a higher percentage of AITC was released from the films to the fatty simulant. This is the most common behavior for active materials with compounds derived from essential oils, which is related to the hydrophobic nature of the compound [ 41 , 42 , 43 ]. In previous sections, it was observed that the surface free energy of materials was dominated by the polar component ( γ S P > γ S D ).…”
Section: Resultsmentioning
confidence: 99%
“…Ethanolic solutions at 10% and 95% v / v were used as aqueous and fatty food simulants, respectively. Even though isooctane is the recommended substitute for fatty simulant (D2) according to EU regulations, ethanol 95% v / v has been widely employed to assess the release of compounds from active materials [ 41 , 42 , 43 ], probably due to the convenience for analytical methods and safety. Pieces of 40 × 5 cm 2 were immersed into 100 mL of simulant at 25 °C and stirred at 150 rpm to prevent the effect of boundary/stagnant layers at the film interface for non-viscous liquids [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…(2019); Chen et al . (2021), respectively. Samples of the same weight were cut and placed in 95% ethanol, sealed with aluminium foil and extracted at 65 °C for 3 hours.…”
Section: Methodsmentioning
confidence: 98%
“…The antioxidant activity of paper was obtained by the ability to scavenge DPPH and ABTS radicals, and experimental methods were referenced to Jiang et al (2019); Chen et al (2021), respectively. Samples of the same weight were cut and placed in 95% ethanol, sealed with aluminium foil and extracted at 65 °C for 3 hours.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The WCA of the film was acquired by referring to the method of Chen et al [22]. The film samples were laid on a contact angle tester table flat.…”
Section: Water Contact Angle (Wca)mentioning
confidence: 99%